In vivo evaluation of crestal bone heights following implant placement with ′flapless′ and ′with-flap′ techniques in sites of immediately loaded implants - Job Shibu; Bhat Vinaya; Naidu E (Wolters Kluwer Medknow Publications, 2008)
Purpose: To evaluate and compare the changes in crestal bone height around implants placed with flapless surgery and with-flap surgery. Materials and Methods: Ten implants were placed in six patients - five using flapless and five using with-flap techniques. Single-piece root-form implants and a one-stage approach with immediate nonfunctional loading protocol were used. The change in heights of crestal bone was measured on standardized digital periapical radiographs taken at 0, 1, and 3 months. Results: On mesial side, the mean change from months 0-1, months 1-3, and months 0-3 for flapless method was significantly lower than with-flap method [0.01-0.06 mm for flapless and 0.13-0.40 mm for with-flap ( P = 0.01)]. On the distal side, the mean change from months 0-1, months 1-3, and months 0-3 for flapless method was significantly lower than with-flap method [0.02-0.05 mm for flapless and 0.09-0.30 mm for with-flap ( P = 0.01)]. Conclusions: During the three-month period, reduction of crestal bone height around the implants placed with flapless surgery (0.06 mm) was not statistically significant, while the reduction of crestal bone height around the implants placed using with-flap surgery (0.4 mm) was statistically significant. Comparitively, flapless approach showed lesser crestal bone height reduction, which was statistically significant.